Implementasi Desain Interior “Taste of Bandeng Elrina” - Susanti, Tan Aprillia; Kusumowidagdo, Astrid; Indrawan, Stephanus Evert (KREASI, 2015)
Indonesian people are accustomed to bring back souvenir for their relatives when they are traveling. This phenomena also occurs in Semarang. Nowadays, Semarang is more developed, where there are many domestic and international tourists are visiting Semarang. As the number of travelers are increasing, the demand for souvenirs shop is also escalating. Although Elrina is facilitated with a restaurant that differs them from the other stores, however it needs a uniqueness that distinguishes them with the others. One of the strategies is by having unique interior design and it can represent the business concept or brand image of the company. Modern interior concept was chosen and it is expected to give an additional value and appeals the customer. The purpose of Elrina restaurant & souvenir store design is to create a different experience and atmosphere for the visitors, therefore they are more interested to shop and dine in Elrina. Interior design uniqueness that covers the function and aesthetic element process with odern concept can be one of selling point factors.